Brill's companion to prequels, sequels, and retellings of classical epic - Simms, Robert. (Brill's Companions to Classical Reception, 2018)
The epics of ancient Greece and Rome are unique in that many went unfinished, or if they were finished, remained open to further narration that was beyond the power, interest, or sometimes the life-span of the poet. Such incompleteness inaugurated a tradition of continuance and closure in their reception. Brill's Companion to Prequels, Sequels, and Retellings of Classical Epic explores this long tradition of continuing epics through sequels, prequels, retellings and spin-offs. This collection of essays brings together several noted scholars working in a variety of fields to trace the persistence of this literary effort from their earliest instantiations in the Iliad and Odyssey of Homer to the contemporary novels of Ursula K. Le Guin and Margaret Atwood.